Comparative Study of Spermatogenesis and Nucleolar Behavior in Testicular Lobes of Euschistus heros (Heteroptera: Pentatomidae) - Hederson Vinicius de Souza; Mary Massumi Itoyama (Psyche: A Journal of Entomology)
In some testicular lobes of the Pentatomidae there may be occurrence of atypical spermatogenesis or polymegaly, leading to the production of nonfertile sperm. The comparative analysis of spermatogenesis and nucleolar behavior in testicular lobes of Euschistus heros showed cells with polymegaly in lobes 4 and 6. Generally, when these lobes are present in the same individual, there is also the formation of atypical cells in the flanking lobe. Such characteristic was not seen in E. heros. However, differences regarding the concentration of heteropyknotic chromatin and silver-positive bodies in this lobe deserve attention. This study explored the literature and demonstrated the prevalence of some lobes in the formation of differentiated cells. It was also found in the literature that there is an association of the chromocenter with the nucleolus in several species of Pentatomidae, but in E. heros this association does not appear to occur.